Hadith #2113 - Sunan Abi Dawud - Abdur Rahman bin Mahdi عبد الرحمن بن مهدي; Amir al-Sha'bi عامر الشعبي; Faras bin Yahya al-Hamdani al-Kharfi فراس بن يحيى; Masrouq bin al-Ajda' مسروق بن الأجدع; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Uthman bin Muhammad (Sunan Abi Dawud)
This is not lawful for anyone after the Messenger of Allah (ﷺ).
Grade: Hasan

Hadith #2114 - Sunan Abi Dawud - Abdur Rahman bin Mahdi عبد الرحمن بن مهدي; Alqama bin Qays علقمة بن قيس بن عبد الله; ibn Mas'ud; Ibrahim al-Nakha'i إبراهيم النخعي; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Uthman bin Muhammad; Yazid bin Harun يزيد بن هارون (Sunan Abi Dawud)
Masruq said on the authority of Abdullah ibn Mas’ud: Abdullah (ibn Mas’ud ) was asked about a man who had married a woman without cohabiting with her or fixing any dower for her till he died. Ibn Mas’ud said: She should receive the full dower (as given to women of her class), observe the waiting period (‘Iddah), and have her share of inheritance. Thereupon Ma’qil ibn Sinan said: I heard the Messenger of Allah (ﷺ) giving the same decision regarding Birwa’ daughter of Washiq (as the
Grade: Sahih

Hadith #2117 - Sunan Abi Dawud - Abu 'Ubaidah ibn al-Jarrah; Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; ibn Mas'ud; Isra'il bin Yonus bin Abi Ishaq إسرائيل بن يونس بن أبي إسحاق; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Abi Dawud)
The Prophet (ﷺ) said to a man: Would you like me to marry you to so-and-so? He said: Yes. He also said to the woman: Would you like me to marry you to so-and-so? She said: Yes. He then married one to the other. The man had sexual intercourse with her, but he did not fix any dower for her, nor did he give anything to her. He was one of those who participated in the expedition to al-Hudaybiyyah. One part of the expedition to al-Hudaybiyyah had a share in Khaybar. When he was nearing his death, h
Grade: Sahih

Hadith #2121 - Sunan Abi Dawud - Abu Bakr bin Muhammad bin 'Amr bin Hazm أبو بكر بن محمد بن عمرو بن حزم; Muhammad bin Abi Bakr bin Muhammad محمد بن أبي بكر بن محمد بن عمرو; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Umm Salamah; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان; Zuhayr bin Harb زهير بن حرب بن شداد أبو خثيمة (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) married me when I was seven years old. The narrator Sulaiman said: or Six years. He had intercourse with me when I was nine years old.
Grade: Sahih

Hadith #2147 - Sunan Abi Dawud - Abu Zara' bin 'Amr /Harm أبو زرعة بن عمرو/هرم; Amr bin Sa'id bin al-As عمرو بن سعيد بن العاص- الأشدق; Jarir bin 'Abdullah al-Bajli; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Yonus bin 'Ubaid bin Dinar يونس بن عبيد بن دينار العبدي (Sunan Abi Dawud)
The Prophet (ﷺ) said: A man will not be asked as to why he beat his wife.
Grade: Hasan

Hadith #2161 - Sunan Abi Dawud - Abu Hurairah; Hanad bin al-Sari bin Mus'ab هناد بن السري بن مصعب; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Suhayl bin Abi Salah سهيل بن أبي صالح; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Abi Dawud)
Ibn ‘Abbas reported the Prophet (ﷺ) as saying “If anyone who means to have intercourse with his wife says “In the name of Allaah, O Allaah, keep us away from the devil and keep the devil away from what You hast provided us.” It will be ordained that no devil will ever harm the child born to them.
Grade: Sahih

Hadith #2162 - Sunan Abi Dawud - Abdur Rahman bin Mahdi عبد الرحمن بن مهدي; Jabir ibn 'Abdullah; Muhammad bin al-Munkdar bin 'Abdullah محمد بن المنكدر بن عبد الله بن الهدير; Muhammad bin Bashar Bindar محمد بن بشار بندار; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Prophet (ﷺ) said: He who has intercourse with his wife through her anus is accursed.
Grade: Hasan

Hadith #2169 - Sunan Abi Dawud - Abdullah bin Abi Najih عبد الله بن أبي نجيح; Abu Sa'id al-Khudri; Mujahid bin Jabir مجاهد بن جبر; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
If a man has sexual intercourse (with menstruating woman) during her bleeding, he should give one dinar as sadaqah, and if he does so when bleeding has stopped, he should give half a dinar as sadaqah.
Grade: Da'if

Hadith #2180 - Sunan Abi Dawud - ibn Umar; Muhammad bin 'Abdur Rahman bin 'Ubaid محمد بن عبد الرحمن بن عبيد القرشي; Salim bin 'Abdullah bin 'Umar سالم بن عبد الله بن عمر بن الخطاب; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Uthman bin Muhammad; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Abi Dawud)
The aforesaid tradition has also been transmitted by Nafi’ through a different chain of narrators. This version says Ibn ‘Umar divorced a wife of his while she was menstruating pronouncing one divorce. He then narrated the rest of the tradition similar to the one narrated by Malik.
Grade: Sahih

Hadith #2200 - Sunan Abi Dawud - Muhammad bin Ibrahim bin al-Harith محمد بن إبراهيم بن الحارث; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Umar ibn al-Khattab; Yahya bin Sa'id al-Ansari يحيى بن سعيد الأنصاري (Sunan Abi Dawud)
Abu al-Sahba’ said to Ibn Abbas: Do you know that a divorce by three pronouncements was made a single one during the time of the Prophet (ﷺ), and of AbuBakr and in the early days of the caliphate of Umar? He replied: Yes.
Grade: Sahih

Hadith #2220 - Sunan Abi Dawud - al-Hakam bin Aban الحكم بن أبان العدني; Ikrama عكرمة; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
A similar tradition has been transmitted by A’ishah through a different chain of narrators.
Grade: Sahih

Hadith #2234 - Sunan Abi Dawud - Aisha bint Abi Bakr; al-Aswad bin Yazid الأسود بن يزيد بن قيس النخعي; Ibrahim al-Nakha'i إبراهيم النخعي; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Muhammad bin Kathir al-'Abdi محمد بن كثير العبدي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
A’ishah said “The Prophet (ﷺ) gave her choice. Her husband was a slave.”
Grade: Sahih

Hadith #2250 - Sunan Abi Dawud - Ahmed bin 'Amr bin al-Sarh أحمد بن عمرو بن السرح أبو الطاهر; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Amr bin 'Uthman عمرو بن عثمان بن عفان; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sahl bin Sa'd bin Malik; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Wahb bin Bayan وهب بن بيان (Sunan Abi Dawud)
The tradition mentioned above has also been transmitted by Sahl bin Sa’d Al Sa’idi through a different chain of narrators. This version has “He divorced her three times before the Messenger of Allah (ﷺ). The Messenger of Allah (ﷺ) implemented it and what is done before the Prophet (ﷺ) is sunnah(model behavior of the Prophet). Sahl said “I attended this before the Messenger of Allah(ﷺ). Afterwards the sunnah about those who invoked curses on each other was established that they (t
Grade: Sahih

Hadith #2259 - Sunan Abi Dawud - Abu Hurairah; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Sa'id bin Abi Sa'id; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The words narrated by Malik alone are: “and he attributed the child to the woman.” Yunus narrated from Al Zuhri on the authority of Sahl bin Sa’d in the tradition regarding li’an(invoking curses). He disowned her conception hence her child was attributed to her.
Grade: Sahih

Hadith #2266 - Sunan Abi Dawud - Aisha bint Abi Bakr; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Urwa ibn al-Zubayr عروة بن الزبير (Sunan Abi Dawud)
The tradition mentioned above has also been transmitted by Muhammad bin Rashid through a different chain of narrators to the same effect. This version adds “he is the child of fornication for the people of his mother whether she was free or a slave. This attribution of a child to the parents was practiced in the beginning of Islam. The property divided before Islam will not be taken into account.
Grade: Hasan

Hadith #2269 - Sunan Abi Dawud - Abd Khayr bin Yazid al-Hamdani عبد خير بن يزيد الهمداني; Abdur-Razzaq عبد الرزاق بن همام; Amir al-Sha'bi عامر الشعبي; Khshysh bin Asrm bin al-'Aswad خشيش بن أصرم بن الأسود; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Zayd bin Arqam (Sunan Abi Dawud)
I was sitting with the Prophet (ﷺ). A man came from the Yemen, and said: Three men from the people of the Yemen came to Ali, quarrelling about a child, asking him to give a decision. They had had sexual intercourse with a woman during a single state of purity. He said to two of them: Give this child to this man (the third person) with pleasure. But they (refused and) cried loudly. Again he said to two of them: Give the child to the man (the third person) willingly. But they (refused and) cried
Grade: Sahih

Hadith #2272 - Sunan Abi Dawud - al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sa'id bin Mnswr bin Sh'bh سعيد بن منصور بن شعبة; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Urwa ibn al-Zubayr عروة بن الزبير (Sunan Abi Dawud)
A’ishah wife of the Prophet (ﷺ) said “Marriage in pre Islamic times was of four kinds.” One of them was the marriage contracted by the people today. A man asked another man to marry his relative (sister or daughter) to him. He fixed the dower and married her to him. Another kind of marriage was that a man asked his wife when she became pure from menstruation to send fro so and so and have sexual intercourse with him. Her husband kept himself aloof and did not have intercourse with her ti
Grade: Sahih

Hadith #2278 - Sunan Abi Dawud - Abdur Rahman bin Abi Layla عبد الرحمن بن أبي ليلى; Muhammad bin 'Isa bin Hyan محمد بن عيسى بن حيان; Muslim bin Salm al-Nahdi, Abu Farwa مسلم بن سالم النهدي أبو فروة; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
Zayd ibn Harithah went out to Mecca and brought the daughter of Hamzah with him. Then Ja’far said: I shall take her; I have more right to her; she is my uncle’s daughter and her maternal aunt is my wife; the maternal aunt is like mother. Ali said: I am more entitled to take her. She is my uncle’s daughter. The daughter of the Messenger of Allah (ﷺ) is my wife, and she has more right to her. Zayd said: I have more right to her. I went out and journeyed to her, and brought her with me. The
Grade: Sahih

Hadith #2287 - Sunan Abi Dawud - Amir al-Sha'bi عامر الشعبي; Fatima bint Qays; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Salmah bin Kahayl al-Hadrami سلمة بن كهيل بن حصين; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
Fatimah daughter of Qais said “I was married to a man of Banu Makhzum. He divorced me absolutely. The narrator then transmitted the rest of the tradition like that of Malik. This version has “Do not marry yourself without my permission.” Abu Dawud said Al Sha’bi, Al Bahiyy and ata from abd Al Rahman bin asim and Abu Bakr bin Abi Al Jahm all narrated on the authority of Fatimah daughter of Qais that her husband had divorced her three times.
Grade: Sahih

Hadith #2292 - Sunan Abi Dawud - Abdur Rahman bin al-Qasim عبد الرحمن بن القاسم بن محمد بن أبي بكر; al-Qasim ibn Muhammad القاسم بن محمد بن أبي بكر الصديق; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Urwa ibn al-Zubayr عروة بن الزبير (Sunan Abi Dawud)
Aisha (Allah be pleased with her) severely objected to the tradition of Fatimah daughter of Qays. She said: Fatimah lived in a desolate house and she feared for her loneliness there. Hence the Messenger of Allah (ﷺ) accorded permission to her (to leave the place).
Grade: Hasan

Hadith #2309 - Sunan Abi Dawud - Amr bin Sharhbayl, Abu Maysara عمرو بن شرحبيل الهمداني أبو ميسرة الكوفي; ibn Mas'ud; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Shaqayq bin Salmah al-Asadi شقيق بن سلمة الأسدي أبو وائل الكوفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) was asked about a man who divorced his wife three times, and she married another who entered upon her, but divorced her before having intercourse with her, whether she was lawful for the former husband. She said: The Prophet (ﷺ) replied: She is not lawful for the first (husband) until she tastes the honey of the other husband and he tastes her honey.
Grade: Sahih

Hadith #2363 - Sunan Abi Dawud - Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Muhammad bin al-Sabah محمد بن الصباح البزاز الدولابي; Sharayk bin 'Abdullah شريك بن عبد الله النخعي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
The Prophet (ﷺ) as saying: Fast is a shield ; when one of you is fasting, he should neither behave in an obscene manner nor foolishly. If a man fights or abuses him, he should say: I am fasting, I am fasting.
Grade: Sahih

Hadith #2373 - Sunan Abi Dawud - Abdur Rahman bin 'Abis al-Nakha'i عبد الرحمن بن عابس النخعي; Abdur Rahman bin Abi Layla عبد الرحمن بن أبي ليلى; Abdur Rahman bin Mahdi عبد الرحمن بن مهدي; Ahmad bin Hanbal أحمد بن حنبل; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) had himself cupped when he was fasting and wearing ihram (pilgrim garb).
Grade: Da'if

Hadith #2375 - Sunan Abi Dawud - Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Zayd bin Aslam زيد بن أسلم (Sunan Abi Dawud)
We would not allow a man who was fasting to get himself cupped due to abomination of hardship.
Grade: Sahih

Hadith #2383 - Sunan Abi Dawud - Aisha bint Abi Bakr; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sa'd bin Ibrahim سعد بن إبراهيم بن عبد الرحمن; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Prophet (ﷺ) used to kiss (me) during the month of fasting.
Grade: Sahih

Hadith #2389 - Sunan Abi Dawud - Abu Hurairah; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Humaid bin 'Abdur Rahman حميد بن عبد الرحمن بن عوف الزهرى; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Muhammad bin 'Isa bin Hyan محمد بن عيسى بن حيان; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
A man said to Messenger of Allah (ﷺ): Messenger of Allah, I was overtaken by dawn while I was sexually defiled, and I want to keep fast. The Messenger of Allah (ﷺ) said: I am also overtaken by dawn while I am in the state of sexual defilement ; I also want to keep fast. I take a bath and I keep fast. The man said: Messenger of Allah, you are not like us ; Allah has forgiven you your past and future sins. The Messenger of Allah (ﷺ) became angry and said: I swear by Allah, I hope I shall be
Grade: Sahih

Hadith #2396 - Sunan Abi Dawud - Abu Hurairah; Ahmad bin Hanbal أحمد بن حنبل; Ammara bin al-Q'aqa' bin Shabrma عمارة بن القعقاع بن شبرمة; Habib al-Ma'lm Abu Muhammad حبيب المعلم أبو محمد البصري; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
The Prophet (ﷺ) said: If anyone breaks his fast one day in Ramadan without a concession granted to him by Allah, a perpetual fast will not atone for it.
Grade: Da'if

Hadith #2400 - Sunan Abi Dawud - ibn Abbas; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sa'id bin Jubayr سعيد بن جبير الأسدي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Uthman bin 'Asim bin Husayn عثمان بن عاصم بن حصين أبو حصين (Sunan Abi Dawud)
The Prophet (ﷺ) as saying: If anyone dies when some fast is due from him (i.e. which he could not keep) his heir must fast on his behalf. Abu Dawud said: This applies to the fast which a man vows ; and this is the opinion of Ahmad b. Hanbal.
Grade: Sahih

Hadith #2454 - Sunan Abi Dawud - Aisha bint Abi Bakr; Aisha bint Talha عائشة بنت طلحة بن عبيد الله التيمى; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Talha bin Yahya bin Talha طلحة بن يحيى بن طلحة; Uthman bin Muhammad; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) said: He who does not determine to fast before dawn does not fast.
Grade: Sahih

Hadith #2460 - Sunan Abi Dawud - Abdur Rahman bin Harmaz al-A'araj عبد الرحمن بن هرمز الأعرج أبو داود; Abu al-Zanad أبو الزناد; Abu Hurairah; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
When one of you receives an invitation (for a meal), he should accept it. If he isn to fasting, he should eat, and if he is fasten, he should pray. Hisham said: The word salat means to pray (for him to Allah). Abu Dawud said: This tradition has also been narrated by Hafs b. Ghiyath from Hisham.
Grade: Sahih

Hadith #2527 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; al-Sa'ib bin Malik السائب بن مالك; Ata'a bin al-Sa'ib al-Thaqifi عطاء بن السائب الثقفي; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) announced an expedition, and I was a very old man and I had no servant. I, therefore, sought a hireling who would serve instead of me, and I would give him his portion. So I found a man. When the time of departure arrived, he came to me and said: I do not know what would be the portions, and how much would be my portion. So offer something (as wages) to me, whether there would be any portion or not. I offered three dinars (as his wages) for him. When some booty arriv
Grade: Sahih

Hadith #2528 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; al-Sa'ib bin Farroukh, Abu al-Abbas السائب بن فروخ أبو العباس الشاعر; Habib bin Abi Thabit حبيب بن أبي ثابت قيس; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
A man came to the Messenger of Allah (ﷺ) and said: I came to you to take the oath of allegiance to you on emigration, and I left my parents weeping. He (the Prophet) said: Return to them and make them laugh as you made them weep.
Grade: Sahih

Hadith #2546 - Sunan Abi Dawud - Abu Hurairah; Abu Zara' bin 'Amr /Harm أبو زرعة بن عمرو/هرم; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) used to name a mare a horse.
Grade: Sahih

Hadith #2563 - Sunan Abi Dawud - Jabir ibn 'Abdullah; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
Anas bin Malik said “I brought my brother when he was born to Prophet(ﷺ) to chew something for him and rub his palate with it and found him in a sheep pen branding the sheep, I think, on their ears.”
Grade: Sahih

Hadith #2589 - Sunan Abi Dawud - al-Sa'ib bin Yazid bin Akht Namr; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Yazid bin 'Abdullah bin Khusayfa يزيد بن عبد الله بن خصيفة (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) prohibited to cut a piece of leather between two fingers.
Grade: Hasan

Hadith #2596 - Sunan Abi Dawud - Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
Ilyas bin Salamah(bin Al Akwa’) said on the authority of his father “We went on an expedition with Abu Bakr (Allaah be pleased with him) in the time of the Apostle of Allaah(ﷺ) and our war cry was “Put to death” “Put to death”.”
Grade: Sahih

Hadith #2611 - Sunan Abi Dawud - Alqama bin Mrthd علقمة بن مرثد; Burayda bin al-Husayb; Muhammad bin Abi Da'ud al-Bghdady محمد بن أبي داود; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Sulaiman bin Burayda bin al-Husayb سليمان بن بريدة بن الحصيب; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Abi Dawud)
The Prophet (ﷺ) said: The best number of companions is four, the best number in expeditions four hundred, and the best number in armies four thousand; and twelve thousand will not be overcome through smallness of numbers. Abu Dawud said: What is correct is that this tradition is mursal (i.e. the link of the Companion is missing).
Grade: Sahih

Hadith #2612 - Sunan Abi Dawud - Alqama bin Mrthd علقمة بن مرثد; Burayda bin al-Husayb; Ibrahim bin Muhammad bin al-Harith إبراهيم بن محمد أبو اسحاق الفزاري; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Sulaiman bin Burayda bin al-Husayb سليمان بن بريدة بن الحصيب (Sunan Abi Dawud)
Sulaiman bin Buraidah reported on the authority of his father. When the Apostle of Allaah(ﷺ) appointed a Commander over an Army or a detachment, he instructed him to fear Allaah himself and consider the welfare of the Muslims who were with him. He then said “When you meet the polytheists who are your enemy, summon them tone of three things and accept whichever of them they are willing to agree to, and refrain from them. Summon them to Islam and if they agree, accept it from them and refrain
Grade: Sahih

Hadith #2649 - Sunan Abi Dawud - Amr bin Dinar عمرو بن دينار الأثرم الجمحي; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Ubaidullah bin Abi Rafi' عبيد الله بن أبي رافع (Sunan Abi Dawud)
Khabbab said “We came to the Apostle of Allaah(ﷺ) while he was reclining on an outer garment in the shade of the Ka’bah. Complaining to him we said “Do you not ask Allaah for help for us? And do you not pray to Allaah for us? He sat aright turning red in his face and said “A man before you (i.e., in ancient times) was caught and a pit was dug for him in the earth and then a saw was brought placed on his head and it was broken into two pieces but that did not turn him away from his rel
Grade: Sahih

Hadith #2651 - Sunan Abi Dawud - Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; Harithh bin Mdrb حارثة بن مضرب; Muhammad bin Bashar Bindar محمد بن بشار بندار; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
‘Ali said “Hatib went and wrote to the people of Makkah that Muhammad (ﷺ) is going to proceed to them. This version has “She said “I have no letter. We made her Camel kneel down, but we did not find any letter with her. ’Ali said “By Him in Whose name oath is taken, I shall kill you or you should bring out the letter. He then narrated the rest of the tradition.
Grade: Sahih

Hadith #2747 - Sunan Abi Dawud - Habib bin Muslama; Makhul al-Shami/al-Damashiqi مكحول الشامي; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Ziyad bin Jariyya bin al-Tamimi زياد بن جارية التميمي الدمشقي (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) went out on the day of Badr along with three hundred and fifteen (men). The Messenger of Allah (ﷺ) said: O Allah, they are on foot, provide mount for them; O Allah , they are naked, clothe them; O Allah, they are hungry, provide food for them. Allah then bestowed victory on them. They returned when they were clothed. There was no man of them but he returned with one or two camels; they were clothed and ate to their fill.
Grade: Hasan

Hadith #2761 - Sunan Abi Dawud - Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; Harithh bin Mdrb حارثة بن مضرب; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
I heard the Messenger of Allah (ﷺ) say when they (messengers sent by Musaylimah) read the letter of Musaylimah: What do you believe yourselves? They said: We believe as he believes. He said: I swear by Allah that were it not that messengers are not killed, I would cut off your heads.
Grade: Sahih

Hadith #2798 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Asim bin Kulayb bin Shahab عاصم بن كليب بن شهاب بن المجنون; Kulayb bin Shahab كليب بن شهاب; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) distributed sacrificial animals among his Companions. He gave me a kid (of less than a year). I took it to him and said: This is a kid. He said: Sacrifice it. so I sacrificed it.
Grade: Hasan Sahih

Hadith #2833 - Sunan Abi Dawud - Amr bin Dinar عمرو بن دينار الأثرم الجمحي; Ata' bin Abi Rabah عطاء بن أبي رباح; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Umm Kurz al-Khuza'iyya (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) used to sacrifice goat out of every fifty goats. Abu Dawud said: Fara’ means the first baby camel born (to the Arabs). They used to sacrifice it for their idols, and then eat it, and its skin was thrown on a tree. ‘Atira was a sacrifice made during the first ten days of Rajab.
Grade: Sahih

Hadith #2834 - Sunan Abi Dawud - Abu Yazid al-Makki أبو يزيد المكي; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Saba' bin Thabit; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Ubaidullah bin Abi Yazid عبيد الله بن أبي يزيد المكي (Sunan Abi Dawud)
I heard the Messenger of Allah (ﷺ) say: Two resembling sheep are to be sacrificed for a boy and one for a girl. AbuDawud said: I heard Ahmad (ibn Hanbal) say: The Arabic word mukafi’atani means equal (in age) or resembling each other.
Grade: Sahih

Hadith #2858 - Sunan Abi Dawud - ibn Abbas; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Wahb bin Munabbih al-Abnavi وهب بن منبه الأبناوي; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
The Prophet (ﷺ) said: Whatever is cut off of an animal when it is alive is dead.
Grade: Sahih

Hadith #2863 - Sunan Abi Dawud - al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Amir bin Sa'd ibn Abi Waqqas عامر بن سعد بن أبي وقاص; Sa'd ibn Abi Waqqas; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Uthman bin Muhammad (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) did not leave dinars, dirhams, camels and goats, nor did he leave will for anything.
Grade: Sahih

Hadith #2875 - Sunan Abi Dawud - Khabbab ibn al-Aratt; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Shaqayq bin Salmah al-Asadi شقيق بن سلمة الأسدي أبو وائل الكوفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Sulaiman al-A'mash الأعمش / سليمان بن مهران (Sunan Abi Dawud)
A man asked him (the Prophet): Messenger of Allah, what are the grave sins? He replied: They are nine. He then mentioned the tradition to the same effect. This version adds: “And disobedience to the Muslim parents, and to violate the sacred House, your qiblah (direction of prayer), in your life and after death.
Grade: Hasan

Hadith #2901 - Sunan Abi Dawud - Abdur Rahman bin 'Abd. bin al-Asbahani عبد الرحمن بن عبد الله بن الأصبهاني; Aisha bint Abi Bakr; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Urwa ibn al-Zubayr عروة بن الزبير; Uthman bin Muhammad; Waki' bin al-Jarrah وكيع بن الجراح; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
I heard the Messenger of Allah (ﷺ) say: I am the heirs of Him who has none, freeing him from his liabilities, and inheriting what he possesses. A maternal uncle is the heir of Him who has none, freeing him from his liabilities, and inheriting his property.
Grade: Hasan Sahih

Hadith #2908 - Sunan Abi Dawud - al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ali bin al-Husain bin 'Ali علي بن الحسين بن علي - زين العابدين; Amr bin 'Uthman عمرو بن عثمان بن عفان; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Usamah ibn Zayd (Sunan Abi Dawud)
On his father’s authority, said that his grandfather reported from the Prophet (ﷺ) something similar.
Grade: Sahih

Hadith #2915 - Sunan Abi Dawud - Aisha bint Abi Bakr; al-Aswad bin Yazid الأسود بن يزيد بن قيس النخعي; Ibrahim al-Nakha'i إبراهيم النخعي; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Uthman bin Muhammad; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Abi Dawud)
‘Aishah, mother of believers (ra), intended to buy a slave-girl to set her free. Her people said: We shall sell her to you on one condition that we shall inherit from her. ‘Aishah mentioned it to the Messenger of Allah (ﷺ). He said: That should not prevent you, for the right of inheritance belongs to the one who has set a person free.
Grade: Sahih

Hadith #2925 - Sunan Abi Dawud - Anas ibn Malik; Asim al-Ahwal عاصم الأحول; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) as saying: There is no alliance in Islam, and Islam strengthened the alliance made during pre-Islamic days.
Grade: Sahih

Hadith #2953 - Sunan Abi Dawud - Ja'far bin Rabi'ya bin Shrhbyl جعفر بن ربيعة بن شرحبيل; Jabir ibn 'Abdullah; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
When the spoils (fai’) came to the Messenger of Allah (ﷺ), he divided it that day ; he gave two portions to a married man and one to a bachelor. The narrator Ibn al-Musaffa added: We were summoned, and I would be summoned before ‘Ammar. So I was summoned and he gave me two portions, for I had a family ; then ‘Ammar b. Yasir was summoned after me and given one.
Grade: Sahih

Hadith #2990 - Sunan Abi Dawud - Amir al-Sha'bi عامر الشعبي; Matruf bin Tarayf al-Harithi مطرف بن طريف; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
Mujja’ah went to the Prophet (ﷺ) asking him for the blood-money of his brother whom Banu Sadus from Banu Dhuhl had killed. The Prophet (ﷺ) said: Had I appointed blood-money for a polytheist, I should have appointed it for your brother. But I shall give you compensation for him. So the Prophet (ﷺ) wrote (a document) for him that he should be given a hundred camels which were to be acquired from the fifth taken from the polytheists of Banu Dhuhl. So he took a part of them, for Banu Dhuhl e
Grade: Da'if

Hadith #2993 - Sunan Abi Dawud - Aisha bint Abi Bakr; Hisham bin 'Urwa هشام بن عروة; Muhammad bin 'Abdullah bin al-Zubair محمد بن عبد الله أبو أحمد الزبيري; Nasr bin 'Ali bin Nasr bin 'Ali; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Urwa ibn al-Zubayr عروة بن الزبير (Sunan Abi Dawud)
Qatadah said “When the Apostle of Allaah(ﷺ) participated in battle there was for him a special portion which he took from where he desired. Safiyyah was from that portion. But when he did not participate himself in his battle, a portion was taken out for him, but he had no choice.”
Grade: Da'if

Hadith #3042 - Sunan Abi Dawud - Amr bin Aws bin Abi Aws عمرو بن أوس بن أبي أوس; Amr bin Dinar عمرو بن دينار الأثرم الجمحي; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
Ibn ‘Abbas said “When the Prophet of the Persians dies, Iblis (satan) led them to Mazdaism.”
Grade: Hasan

Hadith #3046 - Sunan Abi Dawud - Ata'a bin al-Sa'ib al-Thaqifi عطاء بن السائب الثقفي; Muhammad bin 'Ubaid bin Muhammad محمد بن عبيد بن محمد بن واقد; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Abi Dawud)
Harb ibn Ubaydullah told on the authority of his grandfather, his mother’s father, that he had it on the authority of his father that the Messenger of Allah (ﷺ) said: Tithes are to be levied on Jews and Christians, but not on Muslims.
Grade: Da'if

Hadith #3047 - Sunan Abi Dawud - Abdur Rahman bin Mahdi عبد الرحمن بن مهدي; Ata' bin Abi Rabah عطاء بن أبي رباح; Muhammad bin Bashar Bindar محمد بن بشار بندار; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The tradition mentioned above has also been transmitted by Harb bin ‘Ubaid Allah from the Prophet (ﷺ) to the same effect through a different chain of narrators. This version has the word kharaj(land tax) instead of ‘ushr (tithes).
Grade: Da'if

Hadith #3084 - Sunan Abi Dawud - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Prophet (ﷺ) protected Naqi and said: There is no (permission for) protected land except for Allah Most High.
Grade: Sahih

Hadith #3095 - Sunan Abi Dawud - Abdur Rahman bin Mahdi عبد الرحمن بن مهدي; Ahmad bin Hanbal أحمد بن حنبل; Jabir ibn 'Abdullah; Muhammad bin al-Munkdar bin 'Abdullah محمد بن المنكدر بن عبد الله بن الهدير; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
A young Jew became ill. The Prophet (ﷺ) went to visit him. He sat down by his head and said to him: Accept Islam. He looked at his father who was beside him near his head, and he said: Obey Abu al-Qasim. So he accepted Islam, and the Prophet (ﷺ) stood up saying: Praise be to Allah Who has saved him through me from Hell.
Grade: Sahih

Hadith #3104 - Sunan Abi Dawud - Abu Musa al-Asha'ari; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Muhammad bin Kathir al-'Abdi محمد بن كثير العبدي; Shaqayq bin Salmah al-Asadi شقيق بن سلمة الأسدي أبو وائل الكوفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
That her father said: I had a complaint at Mecca. The Messenger of Allah (ﷺ) came to pay a sick-visit to me. He put his hand on my forehead, wiped my chest and belly, and then said: O Allah! heal up Sa’d and complete his immigration.
Grade: Sahih

Hadith #3114 - Sunan Abi Dawud - Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Shaqayq bin Salmah al-Asadi شقيق بن سلمة الأسدي أبو وائل الكوفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Sulaiman al-A'mash الأعمش / سليمان بن مهران; Umm Salamah (Sunan Abi Dawud)
When the time of his death came, he called for new clothes and put on them. He then said: I heard the Messenger of Allah (ﷺ) say: A deceased will be raised in the clothes in which he died.
Grade: Sahih

Hadith #3131 - Sunan Abi Dawud - Abdullah ibn Ja'far; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sa'id bin Masrooq Ath-Thawri سعيد بن مسروق الثوري; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
One of the oaths which the Messenger of Allah (ﷺ) received from us about the virtue was that we would not disobey him in it (virtue): that we would not scratch the face, nor wail, nor tear the front of the garments nor dishevel the hair.
Grade: Sahih

Hadith #3154 - Sunan Abi Dawud - Khabbab ibn al-Aratt; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Shaqayq bin Salmah al-Asadi شقيق بن سلمة الأسدي أبو وائل الكوفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Sulaiman al-A'mash الأعمش / سليمان بن مهران (Sunan Abi Dawud)
Do not be extravagant in shrouding, for I heard the Messenger of Allah (ﷺ) say: Do not be extravagant in shrouding, for it will be quickly decayed.
Grade: Da'if

Hadith #3161 - Sunan Abi Dawud - Abu Hurairah; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Ishaq Mwla Za'id'h إسحاق مولى زائدة; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Suhayl bin Abi Salah سهيل بن أبي صالح (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) said: He who washes the dead should take a bath, and he who carries him should perform ablution.
Grade: Sahih

Hadith #3162 - Sunan Abi Dawud - Aisha bint Abi Bakr; al-Qasim ibn Muhammad القاسم بن محمد بن أبي بكر الصديق; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
This has been abrogated. When Ahmad b. Hanbal was asked about a man taking a bath after his washing the dead, I heard him say: Ablution is sufficient for him. Abu Dawud said: The narrator Abu Salih made a mention of the narrator Ishaq, the client of Za’idah between him and Abu Hurairah. He said: The tradition of Mus’ab is weak. It contains many things that are not practised.
Grade: Sahih

Hadith #3164 - Sunan Abi Dawud - al-Aswad bin Qays al-Bdy الأسود بن قيس العبدي; Jabir ibn 'Abdullah; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The people saw fire (light) in the graveyard and they went there. They found that the Messenger of Allah (ﷺ) was in a grave and he was saying: Give me your companion. This was a man who used to raise his voice while mentioning the name of Allah.
Grade: Hasan

Hadith #3167 - Sunan Abi Dawud - Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sami Maula Abi Bakr bin 'Abdur Rahman سمي مولى أبي بكر بن عبد الرحمن بن الحارث; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
We were forbidden accompany the biers, but it was not stressed upon us.
Grade: Sahih

Hadith #3171 - Sunan Abi Dawud - al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; ibn Umar; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Salim bin 'Abdullah bin 'Umar سالم بن عبد الله بن عمر بن الخطاب; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Prophet (said) said: A bier should not be followed by a loud voice (of wailing) or fire. Abu Dawud said: Harun (one of the narrators) added: “And it should not be preceded (with those) either.”
Grade: Da'if

Hadith #3180 - Sunan Abi Dawud - al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
(I think that the people of Ziyad informed me that he reported on the authority of the Prophet (ﷺ): A rider should go behind the bier, and those on foot should walk behind it, in front of it, on its right and on its left keeping near it. Prayer should be offered over an abortion and forgiveness and mercy supplicated for its parents.
Grade: Sahih

Hadith #3197 - Sunan Abi Dawud - Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sa'd bin Ibrahim سعد بن إبراهيم بن عبد الرحمن; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Talha bin 'Abdullah طلحة بن عبد الله بن عوف الزهري (Sunan Abi Dawud)
Zaid b. Arqam used to utter four takbirs (Allah is Most Great) over our dead person (during prayer). He uttered five takbirs on a dead person. So I asked him. He replied: The Messenger of Allah (ﷺ) used to utter those. Abu Dawud said: I remember the tradition of Ibn al-Muthanna in a more guarded way.
Grade: Sahih

Hadith #3213 - Sunan Abi Dawud - Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Najyh bin Ka'b al-Asady ناجية بن كعب الأسدي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
When the Prophet (ﷺ) placed the dead in the grave, he said: In the name of Allah, and following the Sunnah of the Messenger of Allah (ﷺ). This is Muslim’s version.
Grade: Sahih

Hadith #3215 - Sunan Abi Dawud - Ayoub al-Sakhtiyani أيوب السختياني; Ibrahim bin Muhammad bin al-Harith إبراهيم بن محمد أبو اسحاق الفزاري; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Ansar came to the Messenger of Allah (ﷺ) on the day of Uhud and said: We have been afflicted with wound and fatigue. What do you command us? He said: Dig graves, make them wide, bury two or three in a single grave. He was asked: Which of them should be put first? He replied: The one who knew the Qur’an most. He (Hisham) said: My father Amir died on the day and was buried with two or one.
Grade: Sahih

Hadith #3217 - Sunan Abi Dawud - Habib bin Abi Thabit حبيب بن أبي ثابت قيس; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Shaqayq bin Salmah al-Asadi شقيق بن سلمة الأسدي أبو وائل الكوفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
This tradition has also been transmitted by Sa’d b. Hisham b. ‘Amir with a different chain of narrators.
Grade: Sahih

Hadith #3237 - Sunan Abi Dawud - Amr bin Dinar عمرو بن دينار الأثرم الجمحي; ibn Abbas; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sa'id bin Jubayr سعيد بن جبير الأسدي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) went out to the graveyard and said: Peace be upon you, inhabitants of the dwellings who are of the community of the believers. If Allah wills we shall join you.
Grade: Sahih

Hadith #3303 - Sunan Abi Dawud - Ikrama عكرمة; Mua'wiya bin Hisham al-Qsar معاوية بن هشام القصار; Sa'id bin Masrooq Ath-Thawri سعيد بن مسروق الثوري; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Uqba bin 'Amir al-Juhayni (Sunan Abi Dawud)
The sister of Uqbah ibn Amir took a vow that she would perform hajj on foot, and she was unable to do so. The Prophet (ﷺ) said: Allah is not in need of the walking of your sister. She must ride and offer a sacrificial camel.
Grade: Sahih

Hadith #3335 - Sunan Abi Dawud - Mua'dh bin Mua'dh bin Nsr معاذ بن معاذ بن نصر; Smak bin Hrb bin Aws سماك بن حرب بن أوس; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Suwayd bin Qays al-Tajibi سويد بن قيس التجيبي; Ubaidullah bin Mua'dh عبيد الله بن معاذ بن معاذ بن نصر (Sunan Abi Dawud)
I heard Messenger of Allah (ﷺ) say: Swearing produces a ready sale for a commodity but blots out the blessing. The narrator Ibn al-Sarh said: “for earning”. He also narrated this tradition from Sa’id b. al-Musayyab on the authority of Abu Hurairah from the Prophet (ﷺ).
Grade: Sahih

Hadith #3339 - Sunan Abi Dawud - Hanzala bin Abi Sufyan bin 'Abdur Rahman حنظلة بن أبي سفيان بن عبد الرحمن; ibn Umar; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Tawus bin Kaysan طاوس; Uthman bin Muhammad (Sunan Abi Dawud)
The memory of Sufyan was stronger than mine.
Grade: Sahih

Hadith #3349 - Sunan Abi Dawud - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Abu Qalaba, 'Abdullah bin Zayd al-Jarmi عبد الله بن زيد بن عمرو; Khalid bin Mahran al-Hadha' خالد بن مهران الحذاء; Shrahyl bin Aadah, Abu al-Ash'ath شراحيل بن آدة أبو الأشعث الصنعاني; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Ubada bin As-Samit; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) said: Gold is to be paid for with gold, raw and coined, silver with silver, raw and coined (in equal weight), wheat with wheat in equal measure, barley with barley in equal measure, dates with dates in equal measure, salt by salt with equal measure; if anyone gives more or asks more, he has dealt in usury. But there is no harm in selling gold for silver and silver (for gold), in unequal weight, payment being made on the spot. Do not sell them if they are to be paid f
Grade: Sahih

Hadith #3372 - Sunan Abi Dawud - Ata' bin Abi Rabah عطاء بن أبي رباح; Ibn Jurayj ابن جريج; Jabir ibn 'Abdullah; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
I asked Abu Zinad about the sale of fruits before they were clearly in good condition, and what was said about it. He replied: Urwah ibn az-Zubayr reports a tradition from Sahl ibn Abi Hathmah on the authority of Zayd ibn Thabit who said: The people used to sell fruits before they were clearly in good condition. When the people cut off the fruits, and were demanded to pay the price, the buyer said: The fruits have been smitten by duman, qusham and murad fruit diseases on which they used to dispu
Grade: Sahih

Hadith #3383 - Sunan Abi Dawud - Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Shbyb bin Ghrqd'h شبيب بن غرقدة; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) having said: Allah, Most High, says: “I make a third with two partners as long as one of them does not cheat the other, but when he cheats him, I depart from them.”
Grade: Hasan

Hadith #3385 - Sunan Abi Dawud - Hakim ibn Hizam; Muhammad bin Kathir al-'Abdi محمد بن كثير العبدي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Uthman bin 'Asim bin Husayn عثمان بن عاصم بن حصين أبو حصين (Sunan Abi Dawud)
The tradition mentioned above has also been transmitted by ‘Urwat al-Bariqi through a different chain of narrators. The wordings of this version are different from those of the previous one.
Grade: Sahih

Hadith #3387 - Sunan Abi Dawud - Abu 'Ubaidah ibn al-Jarrah; Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; ibn Mas'ud; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Ubaidullah bin Mua'dh عبيد الله بن معاذ بن معاذ بن نصر; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
I heard the Messenger of Allah (ﷺ) say: If any of you can become like the man who had a faraq of rice, he should become like him. They (the people) asked: Who is the man who had a faraq of rice with him, Messenger of Allah ? Thereupon he narrated the story of the cave when a hillock fell on them (three persons), each of them said: Mention any best work of yours. The narrator said: The third of them said: O Allah, you know that I took a hireling for a faraq of rice. When the evening came, I pre
Grade: Hasan

Hadith #3388 - Sunan Abi Dawud - Amr bin Dinar عمرو بن دينار الأثرم الجمحي; ibn Umar; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Rafi' bin Khadij bin Rafi'; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
I Ammar, and Sa’d became partners in what we would receive on the day of Badr. Sa’d then brought two prisoners, but I and Ammar did not bring anything.
Grade: Da'if

Hadith #3397 - Sunan Abi Dawud - Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Mujahid bin Jabir مجاهد بن جبر; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Usayd bin Zuhayr bin Rafi' (Sunan Abi Dawud)
AbuRafi’ came to us from the Messenger of Allah (ﷺ) said: The Messenger of Allah (ﷺ) forbade us from a work which benefited us; but obedience to Allah and His Apostle (ﷺ) is more beneficial to us. He forbade that one of us cultivates land except the one which he owns or the land which a man lends him (to cultivate).
Grade: Sahih

Hadith #3434 - Sunan Abi Dawud - Jabir ibn 'Abdullah; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Salmah bin Kahayl al-Hadrami سلمة بن كهيل بن حصين; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
Al-Zuhri and Nafi’ differed among themselves in four traditions. This is one of them.
Grade: Sahih

Hadith #3462 - Sunan Abi Dawud - Abdullah bin Abi Najih عبد الله بن أبي نجيح; Abdullah bin Kathir al-Dari عبد الله بن كثير الداري; Abu Ja'far al-Nafaili عبد الله بن محمد أبو جعفر النفيلي الحران; ibn Abbas; Siyar bin Salaama, Abu al-Minhal سيار بن سلامة الرياحي أبو المنهال; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
I heard the Messenger of Allah, (ﷺ) say: When you enter into the inah transaction, hold the tails of oxen, are pleased with agriculture, and give up conducting jihad (struggle in the way of Allah). Allah will make disgrace prevail over you, and will not withdraw it until you return to your original religion.
Grade: Sahih

Hadith #3466 - Sunan Abi Dawud - Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; ibn Umar; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
We made a journey to Syria on an expedition along with the Messenger of Allah (ﷺ). The Nabateans of Syria came to us and we paid in advance to them (in a salam contract) in wheat and olive oil at a specified rate and for a specified time. He asked (by the people): you might have contracted with him who had these things in his possession? He replied: We did not ask them.
Grade: Sahih

Hadith #3495 - Sunan Abi Dawud - Abdullah bin Tawus عبد الله بن طاوس; Abu Bakr bin Abi Uvais أبو بكر بن أبي أويس; ibn Abbas; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Tawus bin Kaysan طاوس; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) forbade to sell grain which one buys by measurement until one receives it in full.
Grade: Sahih

Hadith #3508 - Sunan Abi Dawud - Mhmwd bin Khalid محمود بن خالد; Muhammad bin 'Abdur Rahman محمد بن عبد الرحمن بن نوفل; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) said: Profit follows responsibility.
Grade: Hasan

Hadith #3515 - Sunan Abi Dawud - Abu Ja'far al-Nafaili عبد الله بن محمد أبو جعفر النفيلي الحران; Amr bin al-Shryd عمرو بن الشريد; Ibrahim bin Maysara al-Ta'ifi إبراهيم بن ميسرة الطائفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Prophet (ﷺ) said: When land has been divided and boundaries have been set up, there is no right of pre-emption in it.
Grade: Sahih

Hadith #3527 - Sunan Abi Dawud - Aisha bint Abi Bakr; Amarh bin 'Umayr al-Tymy عمارة بن عمير التيمي; Ibrahim al-Nakha'i إبراهيم النخعي; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
reported the Prophet (ﷺ) as saying: There are people from the servants of Allah who are neither prophets nor martyrs; the prophets and martyrs will envy them on the Day of Resurrection for their rank from Allah, the Most High. They (the people) asked: Tell us, Messenger of Allah, who are they? He replied: They are people who love one another for the spirit of Allah (i.e. the Qur’an), without having any mutual kinship and giving property to one. I swear by Allah, their faces will glow and the
Grade: Sahih

Hadith #3555 - Sunan Abi Dawud - Ata' bin Abi Rabah عطاء بن أبي رباح; Ibn Jurayj ابن جريج; Jabir ibn 'Abdullah; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The life-tenancy which the Messenger of Allah (ﷺ) allowed was only that one should say: It is for you and your descendants. When he says: It is yours as long as you live, it returns to its owner.
Grade: Sahih

Hadith #3556 - Sunan Abi Dawud - Habib bin Abi Thabit حبيب بن أبي ثابت قيس; Jabir ibn 'Abdullah; Mua'wiya bin Hisham al-Qsar معاوية بن هشام القصار; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Uthman bin Muhammad (Sunan Abi Dawud)
The Prophet (ﷺ) said: Do not give property to go to the survivor and do not give life-tenancy. If anyone is given something to the survivor or given life-tenancy, it goes to his heirs.
Grade: Sahih

Hadith #3567 - Sunan Abi Dawud - Aisha bint Abi Bakr; Jasrah bint Dajaja جسرة بنت دجاجة; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) was with one of his wives. One of the Mothers of faithful sent a bowl containing food through a servant of hers. She struck with her hand and broke the bowl. Ibn al-Muthanna’s version has: The Prophet (ﷺ) took the pieces of the bowl, and joined one with the other, and began to collect the food in it, saying: Your mother is jealous. Ibn al-Muthanna added: Eat. They ate till a bowl of the one in whose house he was brought. Abu Dawud said: We then returned to the ve
Grade: Sahih

Hadith #3582 - Sunan Abi Dawud - Hisham bin 'Urwa هشام بن عروة; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Umm Salamah; Urwa ibn al-Zubayr عروة بن الزبير; Zaynab bint Abi Salamah (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) sent me to the Yemen as judge, and I asked: Messenger of Allah, are you sending me when I am young and have no knowledge of the duties of a judge? He replied: Allah will guide your heart and keep your tongue true. When two litigants sit in front of you, do not decide till you hear what the other has to say as you heard what the first had to say; for it is best that you should have a clear idea of the best decision. He said: I had been a judge (for long); or he said (
Grade: Hasan

Hadith #3588 - Sunan Abi Dawud - Abdul Malik bin 'Umayr al-Qabti عبد الملك بن عمير بن سويد القبطي; Abdur Rahman bin Abi Bakra عبد الرحمن بن أبي بكرة; Abu Bakra al-Thaqafi; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) gave the decision that the two adversaries should be made to sit in front of the judge.
Grade: Da'if

Hadith #3633 - Sunan Abi Dawud - Abdur Rahman bin Harmaz al-A'araj عبد الرحمن بن هرمز الأعرج أبو داود; Abu Hurairah; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Prophet (ﷺ) said: If you dispute over a pathway, leave the margin of seven yards.
Grade: Sahih

Hadith #3670 - Sunan Abi Dawud - Abu 'Abdur Rahman al-Salmi أبو عبد الرحمن السلمي; Ata'a bin al-Sa'ib al-Thaqifi عطاء بن السائب الثقفي; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
When the prohibition of wine (was yet to be) declared, Umar said: O Allah, give us a satisfactory explanation about wine. So the following verse of Surat al-Baqarah revealed; “They ask thee concerning wine and gambling. Say: In them is great sin….” Umar was then called and it was recited to him. He said: O Allah, give us a satisfactory explanation about wine. Then the following verse of Surat an-Nisa’ was revealed: “O ye who believe! approach not prayers with a mind befogged….” The
Grade: Sahih

Hadith #3674 - Sunan Abi Dawud - Anas ibn Malik; Isma'il bin 'Abdur Rahman al-Saddi إسماعيل بن عبد الرحمن السدي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Waki' bin al-Jarrah وكيع بن الجراح; Zuhayr bin Harb زهير بن حرب بن شداد أبو خثيمة (Sunan Abi Dawud)
The Prophet (ﷺ) said: Allah has cursed wine, its drinker, its server, its seller, its buyer, its presser, the one for whom it is pressed, the one who conveys it, and the one to whom it is conveyed.
Grade: Sahih

Hadith #3688 - Sunan Abi Dawud - Abu Da'ud أبو داود السجستاني الأزدي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
Malik ibn AbuMaryam said: AbdurRahman ibn Ghanam entered upon us and we discussed tila’ and he said: AbuMalik al-Ash’ari told me that he heard the Messenger of Allah (ﷺ) say: Some of my people will assuredly drink wine calling it by another name.
Grade: Sahih

Hadith #3695 - Sunan Abi Dawud - Ali bin Bdhymh علي بن بذيمة; ibn Abbas; Muhammad bin 'Abdullah bin al-Zubair محمد بن عبد الله أبو أحمد الزبيري; Muhammad bin Bashar Bindar محمد بن بشار بندار; Qays bin Hbtr قيس بن حبتر; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Prophet (ﷺ) said: Do not drink from hollowed stumps, vessel smeared with pitch, pumpkins, and green jars, but drink from a skin which is tied with string. If the drink ferments, lighten it by infusing water. If you are helpless, then pour it away.
Grade: Sahih

Hadith #3698 - Sunan Abi Dawud - Jabir ibn 'Abdullah; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Salm bin Abi al-Ja'd سالم بن أبي الجعد; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
The Prophet (ﷺ) said: I forbade you three things, and now I command (permit) you for them. I forbade you to visit graves, now you may visit them, for in visiting them there is admonition. I forbade you drinks except from skin vessels, but now you may drink from any kind of vessels, but do not drink an intoxicant. I forbade you to eat the meat of sacrificial animals after three days, but now you may eat and enjoy it during your journeys.
Grade: Sahih

Hadith #3719 - Sunan Abi Dawud - Abu Sa'id al-Khudri; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Ubaydullah bin 'Abdullah bin 'Utba عبيد الله بن عبد الله بن عتبة بن مسعود (Sunan Abi Dawud)
The apostle of allah (ﷺ) forbade drinking from the mouth of a water-skin, and riding the animal which feeds on filth and eating the animal which is killed in confinement. Abu Dawud said: Jallalah means an animal which eats filth and impurities.
Grade: Sahih

Hadith #3739 - Sunan Abi Dawud - Jabir ibn 'Abdullah; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The tradition mentioned above has also been transmitted by Nafi’ to the same effect through the chain of narrators as mentioned in Ayyub.
Grade: Sahih

Hadith #3743 - Sunan Abi Dawud - al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Anas ibn Malik; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Wa'il bin Da'ud al-Tymy وائل بن داود التيمي (Sunan Abi Dawud)
The marriage of Zainab daughter of Jahsh was mentioned before Anas b. Malik. He said: I did not see that the Messenger of Allah (ﷺ) held such a wedding feast for any of his wives as he did for her. He held a wedding feast with a sheep.
Grade: Sahih

Hadith #3762 - Sunan Abi Dawud - Abu Hurairah; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Salman Abu Hazam al-Ashja'i سلمان أبو حازم الأشجعي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Sulaiman al-A'mash الأعمش / سليمان بن مهران (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) came out from the valley of a mountain where he had eased himself. There were some dried dates on a shield before us. We called him and he ate with us. He did not touch water.
Grade: Da'if

Hadith #3768 - Sunan Abi Dawud - Abu Juhayfa al-Sawai'; Ali bin al-Aqmar bin 'Amr علي بن الأقمر بن عمرو; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
Umayyah was sitting and a man was eating. He did not mention Allah’s name until there remained the last morsel. When he raised it to his mouth, he said: In the name of Allah at the beginning and at the end of it. The Prophet (ﷺ) laughed and said: The devil kept eating along with him, but when he mentioned Allah’s name, he vomited what was in his belly. Abu Dawud: Jabir bin Subh is grandfather of Sulaiman bin Harb from his mother’s side.
Grade: Hasan

Hadith #3819 - Sunan Abi Dawud - Jabir ibn 'Abdullah; Maharab bin Dithar محارب بن دثار; Mua'wiya bin Hisham al-Qsar معاوية بن هشام القصار; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Uthman bin Muhammad (Sunan Abi Dawud)
The Prophet (ﷺ) was brought a piece of cheese in Tabuk. He called for a knife, mentioned Allah’s name and cut it.
Grade: Hasan

Hadith #3840 - Sunan Abi Dawud - al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; ibn Abbas; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Maymuna bint al-Harith; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Ubaydullah bin 'Abdullah bin 'Utba عبيد الله بن عبد الله بن عتبة بن مسعود (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) sent us on an expedition and made Abu ‘Ubaidah b. al-Jarrah our leader. We had to meet a caravan of the Quraish. He gave us a bag of dates as a light meal during the journey. We had nothing except that. Abu ‘Ubaidah would give each of us one date. We used to suck them as a child sucks, and drink water after that and it sufficed us that day till night. We used to beat leaves off the trees with our sticks (for food), wetted them with water and ate them. We then wen
Grade: Sahih

Hadith #3849 - Sunan Abi Dawud - Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Abu Sa'id al-Khudri; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Abi Dawud)
When the food cloth was removed, the Messenger of Allah (ﷺ) said: “praise be to Allah abundantly and sincerely, of such a nature as is productive of blessing, is not insufficient, Abandoned, or ignored, O our lord.”
Grade: Sahih

Hadith #3852 - Sunan Abi Dawud - Jabir ibn 'Abdullah; Muhammad bin 'Abdullah bin al-Zubair محمد بن عبد الله أبو أحمد الزبيري; Muhammad bin Bashar Bindar محمد بن بشار بندار; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Prophet (ﷺ) said: If anyone spends the night with grease on his hand which he has not washed away, he can blame only himself if some trouble comes to him.
Grade: Sahih

Hadith #3870 - Sunan Abi Dawud - Muhammad bin 'Abdur Rahman b. Abi Dh'ab محمد بن عبد الرحمن بن أبي ذئب; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) prohibited unclean medicine.
Grade: Sahih

Hadith #3874 - Sunan Abi Dawud - Abdullah bin Abi Najih عبد الله بن أبي نجيح; Mujahid bin Jabir مجاهد بن جبر; Sa'd ibn Abi Waqqas; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Prophet (ﷺ) said: Allah has sent down both the disease and the cure, and He has appointed a cure for every disease, so treat yourselves medically, but use nothing unlawful.
Grade: Da'if

Hadith #3876 - Sunan Abi Dawud - al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Ubaydullah bin 'Abdullah bin 'Utba عبيد الله بن عبد الله بن عتبة بن مسعود; Umm Qays bint Mihsan al-Asadi (Sunan Abi Dawud)
He who has a morning meal of seven ‘Ajwah dates will not suffer from any harm that day through poison or magic.
Grade: Sahih

Hadith #3909 - Sunan Abi Dawud - ibn Mas'ud; Isa bin 'Asim al-Asady عيسى بن عاصم الأسدي الكوفي; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Salmah bin Kahayl al-Hadrami سلمة بن كهيل بن حصين; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Zar bin Habaysh bin Habasha زر بن حبيش بن حباشة (Sunan Abi Dawud)
I said: Messenger of Allah! among us there are men who practice divination by drawing lines. He said: There was a Prophet who drew lines, so if anyone does it as he drew lines, that is right.
Grade: Sahih

Hadith #3918 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; Habib bin Abi Thabit حبيب بن أبي ثابت قيس; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Urwa bin 'Amir; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Abi Dawud)
People said: safar is a pain within the belly. I asked: What is hamah ? He said: People said (believed) that hamah which is an owl or a nightbird and which shrieks is the spirit of men. It is not the spirit of men. It is an animal.
Grade: Sahih

Hadith #3927 - Sunan Abi Dawud - al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
On his father’s authority, told that his grandfather reported the Prophet (ﷺ) said: If any slave entered into an agreement to buy his freedom for one hundred uqiyahs and he pays them all but ten, he remains a slave (until he pays the remaining ten); and if a slave entered into an agreement to purchase his freedom for one hundred dinars, and he pays them all but ten dinars, he remains a slave (until he pays the remaining ten). Abu Dawud said: This narrator ‘Abbas al-Jariri is not the same p
Grade: Hasan

Hadith #3967 - Sunan Abi Dawud - Abu al-Darda; Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
“If a man emancipates two Muslim women, they will be deliverance from Hell fire; two bones of their will be emancipation for each of his bone.” Abu Dawud said: Salim did not hear (traditions) from Shurahbil. Shurahbil died at Siffin.
Grade: Sahih

Hadith #3973 - Sunan Abi Dawud - Amr bin Dinar عمرو بن دينار الأثرم الجمحي; Ata' bin Abi Rabah عطاء بن أبي رباح; ibn Abbas; Muhammad bin 'Isa bin Hyan محمد بن عيسى بن حيان; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
I came in the deputation of Banu al-Muntafiq to the Messenger of Allah (ﷺ). He then narrated the rest of the tradition. The Prophet (ﷺ) said: la tahsibanna (do not think) and did not say: la tahsabanna (do not think).
Grade: Sahih

Hadith #3979 - Sunan Abi Dawud - Aslm al-Mnqry Abu Sa'id Hdythh أسلم المنقري; ibn Umar; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Ubayy ibn Ka'b (Sunan Abi Dawud)
The Prophet (ﷺ) read the verse mentioned above, “min du’f.”
Grade: Hasan

Hadith #3988 - Sunan Abi Dawud - Abu Hurairah; Ahmed bin 'Ubda bin Musa أحمد بن عبدة بن موسى; Amr bin Dinar عمرو بن دينار الأثرم الجمحي; Ikrama عكرمة; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
I came to the Prophet (ﷺ). He then narrated the rest of the tradition. A man from the people said: “Messenger of Allah! tell us about Saba’; what is it: land or woman? He replied: It is neither land nor woman; it is a man to whom ten children of the Arabs were born: six of them lived in the Yemen and four lived in Syria. The narrator Uthman said al-Ghatafani instead of al-Ghutayfi. He said: It has been transmitted to us by al-Hasan ibn al-Hakam an-Nakha’i.
Grade: Hasan Sahih

Hadith #3994 - Sunan Abi Dawud - Abdul Malik bin Abd عبد الملك بن عبد الرحمن; Ahmed bin Salah al-Masri أحمد بن صالح المصري; Jabir ibn 'Abdullah; Muhammad bin al-Munkdar bin 'Abdullah محمد بن المنكدر بن عبد الله بن الهدير; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Prophet (ﷺ) used to read the verse “Is there any that will receive admonition (muddakir)? ” that is with doubling of consonant . Abu Dawud said: The word muddakir may be pronounced as mim (m) with a short vowel u. (dal)(d) with a short vowel and kaf (k) with a short vowel i.
Grade: Sahih

Hadith #4052 - Sunan Abi Dawud - Aisha bint Abi Bakr; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Urwa ibn al-Zubayr عروة بن الزبير (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) once prayed wearing a garment having marks. He looked at its marks. When he saluted, he said: Take this garment of mine to AbuJahm, for it turned my attention just now in my prayer, and bring a simple garment without marks. Abu Dawud said: The name of Abu Jahm b. Hudhaifah from Banu ‘Adi b. Ka’b b. Ghanam
Grade: Sahih

Hadith #4087 - Sunan Abi Dawud - Abu Dharr al-Ghaffari; Kharsha bin al-Hurr al-Fazari; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Sulaiman al-A'mash الأعمش / سليمان بن مهران; Sulaiman bin Ms'hr al-Fzary; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
The Prophet (ﷺ) as saying: There are three to whom Allah will not speak and at whom He will not look on the Day of Resurrection, and whom He will not declare pure, and they will have a painful punishment. I asked: Who are they, Messenger of Allah, they are losers and disappointed ? He repeated it three times. I asked: Who are they. Messenger of Allah, they are losers and disappointed ? He replied: The one who wears a trailing robe, the one who takes account of what he gives, and the one who pr
Grade: Sahih

Hadith #4098 - Sunan Abi Dawud - Abdullah bin 'Ubaidullah b. Abi Mulayka عبد الله بن عبيد الله بن أبي مليكة; Ibn Jurayj ابن جريج; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) cursed the man who dressed like a woman and the woman who dressed like a man.
Grade: Sahih

Hadith #4114 - Sunan Abi Dawud - Abdur Rahman bin Mahdi عبد الرحمن بن مهدي; Habib bin Abi Thabit حبيب بن أبي ثابت قيس; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Umm Salamah; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان; Zuhayr bin Harb زهير بن حرب بن شداد أبو خثيمة (Sunan Abi Dawud)
On his father’s authority, said that his grandfather reported the Prophet (ﷺ) said: When one of you marries his female servant to his slave or to his employee, he should not look at her private part below the navel and above the knees. Abu Dawud said: The correct name is Sawwad b. Dawud al-Muzani al-Sairafi (and not Dawud b. Sawwad as mentioned in the chain). The narrator waki’ misunderstood it.
Grade: Hasan

Hadith #4118 - Sunan Abi Dawud - Bakr bin 'Amr Abu al-Siddique al-Naji بكر بن عمرو/ قيس; ibn Umar; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان; Zayd bin al-Hwary Abu زيد بن الحواري أبو الحواري (Sunan Abi Dawud)
Ibn Ishaq and Ayyub b. Musa transmitted it from Nafi’ from Safiyyah.
Grade: Sahih

Hadith #4122 - Sunan Abi Dawud - ibn Abbas; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Zayd bin Aslam زيد بن أسلم (Sunan Abi Dawud)
Al-Zuhri used to deny tanning and say: Some good can be got out of it in any condition Abu Dawud said: Al-Auza’i, Yunus and ‘Uqail did not mention tanning. al-Zubaidi, Sa’id b. ‘Abd al-Aziz and Hafs b. ‘Abd al-‘Aziz mentioned tanning.
Grade: Da'if

Hadith #4173 - Sunan Abi Dawud - Abu Hurairah; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Prophet (ﷺ) said: If a woman uses perfume and passes the people so that they may get its odour, she is so-and-so, meaning severe remarks.
Grade: Hasan

Hadith #4182 - Sunan Abi Dawud - Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; al-Bara' bin Azib bin al-Harith; Muhammad bin Abi Da'ud al-Bghdady محمد بن أبي داود; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Abi Dawud)
A man came to the Messenger of Allah (ﷺ) and he had the mark of yellowness (of saffron). The Prophet (peace be upon him rarely mentioned a thing which he disliked before a man. When he went away, he said: Would that you tell this man that he should wash this off him.
Grade: Da'if

Hadith #4189 - Sunan Abi Dawud - Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Asim bin Kulayb bin Shahab عاصم بن كليب بن شهاب بن المجنون; Kulayb bin Shahab كليب بن شهاب; Mua'wiya bin Hisham al-Qsar معاوية بن هشام القصار; Sufyan bin 'Uqba al-Swa'iy سفيان بن عقبة السوائي الكوفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Wa'il bin Hujr al-Kundi al-Hadrami (Sunan Abi Dawud)
When I parted the hair of the Messenger of Allah (ﷺ) I made a parting from the crow of his head and let his forelock hang between his eyes.
Grade: Hasan

Hadith #4190 - Sunan Abi Dawud - Abdullah bin Abi Najih عبد الله بن أبي نجيح; Abu Ja'far al-Nafaili عبد الله بن محمد أبو جعفر النفيلي الحران; Mujahid bin Jabir مجاهد بن جبر; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
I came to the Prophet (ﷺ) and I had long hair. When the Messenger of Allah (ﷺ) saw me, he said: Evil, evil! He said: I then returned and cut them off. I then came to him in the morning. He said (to me): I did not intend to do evil to you. This is much better.
Grade: Sahih

Hadith #4197 - Sunan Abi Dawud - al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sa'id bin Abi Sa'id; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
Al-Hajjaj ibn Hassan said: We entered upon Anas ibn Malik. My sister al-Mughirah said: You were a boy in those days and you had two locks of hair. He (Anas) rubbed your head and invoked blessing on you. He said: Shave them (i.e. the locks) or clip them, for this is the fashion of the Jews.
Grade: Da'if

Hadith #4202 - Sunan Abi Dawud - Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Sulayman ibn Yasar سليمان بن يسار مولى ميمونة بنت الحارث (Sunan Abi Dawud)
Do not pluck out grey hair. If any believer grows a grey hair in Islam, he will have light on the Day of Resurrection. (This is Sufyan’s version). Yahya’s version says: Allah will record on his behalf a good deed for it, and will blot out a sin for it.
Grade: Hasan Sahih

Hadith #4207 - Sunan Abi Dawud - Abdur Rahman bin Mahdi عبد الرحمن بن مهدي; Iyad bin Laqayt al-Sadusi إياد بن لقيط; Muhammad bin Bashar Bindar محمد بن بشار بندار; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
My father said to him (the Prophet): Show me what is on your back, for I am a physician. He (the Prophet) said: You are only a soother. Its physician is He Who has created it.
Grade: Sahih

Hadith #4253 - Sunan Abi Dawud - Abdur Rahman bin Mahdi عبد الرحمن بن مهدي; ibn Mas'ud; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Muhammad bin Abi Da'ud al-Bghdady محمد بن أبي داود; Raba'i bin Harash bin Jahsh ربعي بن حراش; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Prophet (ﷺ) said: Allah has protected you from three things: that your Prophet should not invoke a curse on you and should all perish, that those who follow what is false should not prevail over those who follow the truth, and that you should not all agree in an error.
Grade: Da'if

Hadith #4274 - Sunan Abi Dawud - Abdur Rahman bin Mahdi عبد الرحمن بن مهدي; Ahmad bin Hanbal أحمد بن حنبل; al-Mughira bin al-Nu'man al-Nakha'i المغيرة بن النعمان النخعي الكوفي; ibn Abbas; Sa'id bin Jubayr سعيد بن جبير الأسدي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The verse: “Those who invoke not with Allah” applied to polytheists. He said: About them another verse, “Say: O my servants who have transgressed against their souls” was also revealed.
Grade: Sahih

Hadith #4281 - Sunan Abi Dawud - Abu Bakr bin 'Ayyash al-Asadi أبو بكر بن عياش بن سالم الأسدي; Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Ahmed bin Ibrahim bin Kathir أحمد بن إبراهيم بن كثير; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Ubaidullah bin Musa bin Abi al-Mukhtar عبيد الله بن موسى بن أبي المختار باذام; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان; Za'ida bin Qadama al-Thaqifi زائدة بن قدامة الثقفي (Sunan Abi Dawud)
When he came back to his home. the Quraish came to him and said: Then what will happen ? He said: Then turmoil will prevail.
Grade: Sahih

Hadith #4375 - Sunan Abi Dawud - Aslam Client Of 'Umar أسلم مولى عمر; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان; Zayd bin Aslam زيد بن أسلم (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) Said: Forgive the people of good qualities their slips, but not faults to which prescribed penalties apply.
Grade: Sahih

Hadith #4402 - Sunan Abi Dawud - Abdul Malik bin 'Umayr al-Qabti عبد الملك بن عمير بن سويد القبطي; Atyh al-Qrzy Bdm; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
AbuZubyan said: A woman who had committed adultery was brought to Umar. He gave orders that she should be stoned. Ali passed by just then. He seized her and let her go. Umar was informed of it. He said: Ask Ali to come to me. Ali came to him and said: Commander of the Faithful, you know that the Messenger of Allah (ﷺ) said: There are three (people) whose actions are not recorded: A boy till he reaches puberty, a sleeper till he awakes, a lunatic till he is restored to reason. This is an idiot
Grade: Sahih

Hadith #4548 - Sunan Abi Dawud - Abdullah bin Abi Najih عبد الله بن أبي نجيح; Abu Ja'far al-Nafaili عبد الله بن محمد أبو جعفر النفيلي الحران; Mujahid bin Jabir مجاهد بن جبر; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The tradition mentioned above has also been transmitted by Khalid through the same chain of narrators to the same effect.
Grade: Sahih

Hadith #4551 - Sunan Abi Dawud - Abu al-Ahwus, Salam bin Sulaym al-Hanafi أبو الأحوص سلام بن سليم الحنفي; Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; Ali ibn Abi Talib; Asim bin Dmrh al-Slwly عاصم بن ضمرة السلولي الكوفي; Hanad bin al-Sari bin Mus'ab هناد بن السري بن مصعب; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The bloodwit for unintentional murder which resembles intentional is twenty-five she camels which entered their fourth year, twenty five she-camels which had entered their fifth year, twenty five she-camels which had entered their third year, and twenty five camels which had entered their second year.
Grade: Da'if

Hadith #4571 - Sunan Abi Dawud - Amr bin Dinar عمرو بن دينار الأثرم الجمحي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Tawus bin Kaysan طاوس (Sunan Abi Dawud)
Hammad b. Zaid and Hammad b. Salamah transmitted it from Hisham b. ‘Arubah on his father’s authority who said that ‘Umar said…
Grade: Sahih

Hadith #4591 - Sunan Abi Dawud - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Prophet (ﷺ) said: If anyone is killed blindly or, when people are throwing stones, by a stone or a whip, his blood-wit is the blood-wit for an accidental murder. But if anyone is killed intentionally, retaliation is due. If anyone tries to prevent it, the curse of Allah, of angels, and of all the people will rest on him.
Grade: Sahih

Hadith #4603 - Sunan Abi Dawud - Abu Ja'far al-Nafaili عبد الله بن محمد أبو جعفر النفيلي الحران; Abu Rafi'; Ahmad bin Hanbal أحمد بن حنبل; Salm Abi al-Nadr سالم بن أبي أمية - أبو النضر; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Ubaidullah bin Abi Rafi' عبيد الله بن أبي رافع (Sunan Abi Dawud)
The Prophet (ﷺ) said: Controverting about the Qur’an is disbelief.
Grade: Hasan Sahih

Hadith #4608 - Sunan Abi Dawud - al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Amir bin Sa'd ibn Abi Waqqas عامر بن سعد بن أبي وقاص; Sa'd ibn Abi Waqqas; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Uthman bin Muhammad (Sunan Abi Dawud)
“Beware! The extremists perished,” saying it three times.
Grade: Sahih

Hadith #4610 - Sunan Abi Dawud - al-Nadr bin Shumayl al-Maazni النضر بن شميل المازني أبو الحسن النحوي; al-Rabi' bin Sulaiman الربيع بن سليمان; Asad bin Musa - Asad al-Sunnah أسد بن موسى بن إبراهيم - أسد السنة; Hanad bin al-Sari bin Mus'ab هناد بن السري بن مصعب; Hmad bin Dlyl حماد بن دليل; Imran bin Milhan, Abu Raja' al-Atardi عمران بن ملحان أبو رجاء العطاردي; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Qabaysa bin 'Uqba bin Muhammad قبيصة بن عقبة بن محمد بن سفيان; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Muslim who offends most against the Muslims is he who enquires about something which has not been forbidden to men, and it is declared forbidden because of his enquiry.
Grade: Sahih

Hadith #4617 - Sunan Abi Dawud - Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Muhammad bin Kathir al-'Abdi محمد بن كثير العبدي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
Al-Hasan used to say that his fall from the heaven on the earth is dearer to him than uttering: The matter is in my hand.
Grade: Da'if

Hadith #4618 - Sunan Abi Dawud - Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin 'Uyaynah سفيان بن عيينة; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
Al-Hasan came to us. The jurists of Mecca told me that I should speak to him that some day he should hold a meeting for them and preach to them. He said: Yes. So they gathered and he addressed them. I did not see anyone on orator greater than him. A man said: Abu Sa’id, who created Satan? He replied: Glory be to Allah! Is there any creator other than Allah? Allah created Satan, and he created good and created evil. The man said: May Allah ruin them! How do they lie to this old man.
Grade: Sahih

Hadith #4627 - Sunan Abi Dawud - Jami' bin Abi Rashid جامع بن أبي راشد الكاهلي; Muhammad bin 'Ali bin al-Hanfiyyah محمد بن الحنفية; Muhammad bin al-Salt al-Basri محمد بن الصلت البصري; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
We used to say in the times of the Prophet (ﷺ): We do not compare anyone with Abu Bakr. ’Umar came next and then ‘Uthman. We then would leave (rest of) the companions of the Prophet (ﷺ) without treating any as superior to other.
Grade: Sahih

Hadith #4628 - Sunan Abi Dawud - Muhammad bin Mskyn bin Nmylh محمد بن مسكين بن نميلة; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
When the Messenger of Allah (ﷺ) was alive, we used to say: The most excellent member of the community of the Prophet (ﷺ) after himself is Abu Bakr, then ‘Umar, then ‘Uthman.
Grade: Sahih

Hadith #4629 - Sunan Abi Dawud - Aabad al-Smak عباد السماك; Qabaysa bin 'Uqba bin Muhammad قبيصة بن عقبة بن محمد بن سفيان; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
I said to my father: Which of the people after the Messenger of Allah (ﷺ) is best? He replied: Abu Bakr. I then asked: Who comes next? He said: ‘Umar. I was then afraid of asking him who came next, and he might mention ‘Uthman, so I said: You came next, O my father? He said: I am only a man among the Muslims.
Grade: Sahih

Hadith #4646 - Sunan Abi Dawud - Abdullah bin Idris bin Yazid al-Audi عبد الله بن إدريس بن يزيد الأودي; Abdullah bin Zalm عبد الله بن ظالم التميمي المازني; Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Hilal bin Yasaf هلال بن يساف; Husayn bin 'Abdur Rahman al-Salmi حصين بن عبد الرحمن السلمي; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Sa'id bin Zayd; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Prophet (ﷺ) said: The Caliphate of Prophecy will last thirty years; then Allah will give the Kingdom of His Kingdom to anyone He wills. Sa’id told that Safinah said to him: Calculate Abu Bakr’s caliphate as two years, ‘Umar’s as ten, ‘Uthman’s as twelve and ‘Ali so and so. Sa’id said: I said to Safinah: They conceive that ‘Ali was not a caliph. He replied: The buttocks of Marwan told a lie.
Grade: Hasan Sahih

Hadith #4676 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; Jabir ibn 'Abdullah; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Abi Dawud)
Faith has over seventy branches, the most excellent of which is the declaration that there is no god but Allah, and the humblest of which is the removal of a bone from the road. And modesty is a branch of faith.
Grade: Sahih

Hadith #4678 - Sunan Abi Dawud - ibn Abbas; Ikrama عكرمة; Muhammad bin Abi Da'ud al-Bghdady محمد بن أبي داود; Smak bin Hrb bin Aws سماك بن حرب بن أوس; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Abi Dawud)
Between a servant and unbelief there is the abandonment of prayer.
Grade: Sahih

Hadith #4690 - Sunan Abi Dawud - Hudhayfah ibn al-Yaman; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Umar bin Muhammad bin Zayd عمر بن محمد بن زيد بن عبد الله (Sunan Abi Dawud)
The Prophet (ﷺ) said: When a man commits fornication, faith departs from him and there is something like a canvas roof over his head; and when he quits that action, faith returns to him.
Grade: Sahih

Hadith #4695 - Sunan Abi Dawud - Alqama bin Mrthd علقمة بن مرثد; Mhmwd bin Khalid محمود بن خالد; Muhammad bin Yusuf al-Faryabi محمد بن يوسف الفريابي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Sulaiman bin Burayda bin al-Husayb سليمان بن بريدة بن الحصيب (Sunan Abi Dawud)
The first to speak on Divine decree in al-Basrah was Ma`bad al Juhani. I and Humaid b. `Abd al-Rahman al-Himyari proceeded to perform Hajj or `Umrah. We said : would that we meet any of the Companions of the Messenger of Allah (ﷺ) so that we could ask him about what they say with regard to divine decree. So Allah helped us to meet `Abd Allah b. `Umar who was entering the mosque. So I and my companion surrounded him, and I thought that my companion would entrust me the task of speaking to him.
Grade: Sahih

Hadith #4697 - Sunan Abi Dawud - Abdullah bin al-Dayli; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Wahb bin Khalid al-Hmyry Abu وهب بن خالد الحميري (Sunan Abi Dawud)
What is Islam? He replied : It means saying prayer, payment of zakat, performing HAJJ, fasting during RAMADAN, and taking a bath on account of sexual defilement. Abu Dawud said: ‘Alqamah was a Murji’i.
Grade: Sahih

Hadith #4699 - Sunan Abi Dawud - Ahmed bin Salah al-Masri أحمد بن صالح المصري; Amr bin Dinar عمرو بن دينار الأثرم الجمحي; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sufyan bin 'Uyaynah سفيان بن عيينة; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Tawus bin Kaysan طاوس (Sunan Abi Dawud)
I went to Ubayy b. Ka’b and said him : I am confused about Divine decree, so tell me something by means of which Allah may remove the confusion from my mind. He replied : were Allah to punish everyone in the heavens and in the earth. He would do so without being unjust to them, and were he to show mercy to them his mercy would be much better than their actions merited. Were you to spend in support of Allah’s cause an amount of gold equivalent to Uhud, Allah would not accept it from you till
Grade: Sahih

Hadith #4711 - Sunan Abi Dawud - Aisha bint Abi Bakr; Aisha bint Talha عائشة بنت طلحة بن عبيد الله التيمى; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Talha bin Yahya bin Talha طلحة بن يحيى بن طلحة (Sunan Abi Dawud)
Allah knows best about what they were doing.
Grade: Sahih

Hadith #4728 - Sunan Abi Dawud - Abu Hurairah; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Suhayl bin Abi Salah سهيل بن أبي صالح (Sunan Abi Dawud)
I heard Abu Hurairah recite this verse : “Allah doth command you to render back your trusts to those to whom they are due” up to “For Allah is he who heareth and seeth all things”. He said : I saw the Messenger of Allah (May peace be upon him) putting his thumb on his ear and finger on his eye. Abu Hurairah said : I saw the Messenger of Allah (May peace be upon him) reciting this verse and putting his fingers. Ibn Yunus said that al-Muqri said. “Allah hears and sees” means that Allah
Grade: Sahih

Hadith #4762 - Sunan Abi Dawud - Abdur Rahman bin Abi Na'm عبد الرحمن بن أبي نعم; Abu Sa'id al-Khudri; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sa'id bin Masrooq Ath-Thawri سعيد بن مسروق الثوري; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
various corruptions will arise in my community, so strike with sword the one who tries to cause separation in the matter of Muslims when they are united, whoever he be.
Grade: Sahih

Hadith #4765 - Sunan Abi Dawud - Khaythama bin 'Abdur Rahman خيثمة بن عبد الرحمن بن أبي سبرة; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Sulaiman al-A'mash الأعمش / سليمان بن مهران; Suwayd bin Ghaflah bin Awsajah سويد بن غفلة بن عوسجة (Sunan Abi Dawud)
The Prophet (ﷺ) said: Soon there will appear disagreement and dissension in my people; there will be people who will be good in speech and bad in work. They recite the Qur’an, but it does not pass their collar-bones. They will swerve from the religion as an animal goes through the animal shot at. They will not return to it till the arrow comes back to its notch. They are worst of the people and animals. Happy is the one who kills them and they kill him. They call to the book of Allah, but th
Grade: Sahih

Hadith #4769 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
Search for the man with crippled hand. He then mentioned the rest of the tradition. This version has: They took him out from beneath the slain in the dust. Abu al-wadi said: As if I am looking at an Abyssinian with a shirt on him. He had one of his hands like the nipple of the female breast, having hair on it like the hair on the tail of the jerboa.
Grade: Sahih

Hadith #4788 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Bashr bin Rafa'i al-Harithy بشر بن رافع الحارثي; Hjaj bin Frafs'h حجاج بن فرافصة الباهلي; Muhammad bin 'Abdullah bin al-Zubair محمد بن عبد الله أبو أحمد الزبيري; Muhammad bin Abi Sari محمد بن أبي السري; Nasr bin 'Ali bin Nasr bin 'Ali; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan Abi Dawud)
When the Prophet (ﷺ) was informed of anything of a certain man, he would not say: What is the matter with so and so that he says? But he would say: What is the matter with the people that they say such and such?
Grade: Sahih

Hadith #4789 - Sunan Abi Dawud - Aisha bint Abi Bakr; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Muhammad bin al-Munkdar bin 'Abdullah محمد بن المنكدر بن عبد الله بن الهدير; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Urwa ibn al-Zubayr عروة بن الزبير (Sunan Abi Dawud)
A man who had the mark of yellowness on him came to the Messenger of Allah (ﷺ). The apostle of Allah (ﷺ) rarely mentioned anything of a man which he disliked before him. When he went out, he said: Would that you asked him to wash it from him. Abu Dawud said: Salam is not ‘Alawi (from the descendants of ‘Ali). He used to foretell events by stars. He bore witness before ‘Abi b. Arafat to the visibility of moon, but he did not accept his witness.
Grade: Da'if

Hadith #4799 - Sunan Abi Dawud - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Harithh bin Wahb al-Khza'y; Ma'bad bin Khalid al-Jadli معبد بن خالد الجدلي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Uthman bin Muhammad; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Abi Dawud)
The Prophet (ﷺ) said: There is nothing heavier than good character put in the scale of a believer on the Day of Resurrection. Abu al-Walid said: I heard ‘Ata al-Kaikharani say: Abu Dawud said: His name is ‘Ata b. Ya’qub. He is the maternal uncle of Ibrahim b. Nafi’. He is called Kaikharani or Kukharani.
Grade: Sahih

Hadith #4802 - Sunan Abi Dawud - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Hamam bin Munabbih همام بن منبه بن كامل; Ibrahim al-Nakha'i إبراهيم النخعي; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Abi Dawud)
The she-camel of the Messenger of Allah (ﷺ) called al-Adba’ had not been outstripped by another, but an A`rabi (a nomadic Arab) came on a young riding camel of his and it outstripped it. That distressed the companions of the Messenger of Allah (ﷺ), but he said: It is Allah’s right that nothing should become exalted in the world but he lowers it.
Grade: Sahih

Hadith #4834 - Sunan Abi Dawud - al-Sa'ib bin Yazid bin Akht Namr; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Mujahid bin Jabir مجاهد بن جبر; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
The spirits are in marshaled hosts; those who know one another will be friendly, and those who do not, will keep apart.
Grade: Sahih

Hadith #4837 - Sunan Abi Dawud - al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Urwa ibn al-Zubayr عروة بن الزبير; Usamah ibn Zayd; Uthman bin Muhammad; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Abi Dawud)
When the Messenger of Allah (ﷺ) sat talking (to the people), he would often raise his eyes to the sky.
Grade: Da'if

Hadith #4848 - Sunan Abi Dawud - Jabir bin Samra; Smak bin Hrb bin Aws سماك بن حرب بن أوس; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Umar bin Sa'd bin 'Ubaid عمر بن سعد بن عبيد أبو داود; Uthman bin Muhammad (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) came upon me when I was sitting thus: having my left hand behind my back and leaning on the fleshy part of it, and said: Are you sitting in the manner of those with whom Allah is angry?
Grade: Sahih

Hadith #4870 - Sunan Abi Dawud - Abdur Rahman bin Harmaz al-A'araj عبد الرحمن بن هرمز الأعرج أبو داود; Abu al-Zanad أبو الزناد; Abu Hurairah; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The most serious breach of trust in Allah’s sight is that a man who has intercourse with his wife, and she with him, spreads her secret.
Grade: Da'if

Hadith #4873 - Sunan Abi Dawud - Abu Hudhayfa al-Nahdi موسى بن مسعود أبو حذيفة النهدي; Aisha bint Abi Bakr; Ali bin al-Aqmar bin 'Amr علي بن الأقمر بن عمرو; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
The Prophet (ﷺ) said: He who is two-faced in this world will have two tongues of fire on the Day of Resurrection.
Grade: Sahih

Hadith #4886 - Sunan Abi Dawud - Isa bin Muhammad bin al-Nahas عيسى بن محمد بن النحاس; Mu'awiya ibn Abu Sufyan; Muhammad bin Yusuf al-Faryabi محمد بن يوسف الفريابي; Rashid bin Sa'd راشد بن سعد; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Thur bin Zayd al-Dayli ثور بن زيد (Sunan Abi Dawud)
Is one of you helpless to be like AbuDaygham or Damdam (Ibn Ubayd is doubtful) who would say when morning came: O Allah, I gave my honour as alms to Thy servants?
Grade: Da'if

Hadith #4895 - Sunan Abi Dawud - Abdul A'ala bin Hamad bin Nasr al-Bahli عبد الأعلى بن حماد بن نصر الباهلي النرسي; Abu Hurairah; Muhammad bin Ajlan al-Madni محمد بن عجلان المدني; Sa'id bin Abi Sa'id; Safwan bin 'Isa al-Zhry صفوان بن عيسى الزهري أبو محمد البصري; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Prophet (ﷺ) said: Allah has revealed to me that you must be humble, so that no one oppresses another and boasts over another.
Grade: Sahih

Hadith #4907 - Sunan Abi Dawud - Aisha bint Abi Bakr; Ata' bin Abi Rabah عطاء بن أبي رباح; Habib al-Ma'lm Abu Muhammad حبيب المعلم أبو محمد البصري; Mua'dh bin Mua'dh bin Nsr معاذ بن معاذ بن نصر; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Ubaidullah bin Mua'dh عبيد الله بن معاذ بن معاذ بن نصر (Sunan Abi Dawud)
I heard the Messenger of Allah (May peace be upon him) say: Men given to cursing will not be witnesses or intercessors.
Grade: Sahih

Hadith #4912 - Sunan Abi Dawud - Abu Hurairah; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Muhammad bin al-Sabah محمد بن الصباح البزاز الدولابي; Salman Abu Hazam al-Ashja'i سلمان أبو حازم الأشجعي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Yazid bin Harun يزيد بن هارون (Sunan Abi Dawud)
The Prophet (ﷺ) said: It is not allowable for a believer to keep from a believer for more than three days. If three days pass, he should meet him and give him a salutation, and if he replies to it they will both have shared in the reward; but if he does not reply he will bear his sin (according to Ahmad’s version) and the one who gives the salutation will have come forth from the sin of keeping apart.
Grade: Da'if

Hadith #4918 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Ahmed bin Muhammad bin Musa al-Samsar أحمد بن محمد بن موسى السمسار; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Humaid bin 'Abdur Rahman حميد بن عبد الرحمن بن عوف الزهرى; Ma'mar bin Rashid معمر بن راشد; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Nasr bin 'Ali bin Nasr bin 'Ali; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Umm Kulthum bint 'Uqba (Sunan Abi Dawud)
The Prophet (ﷺ) said: The believer is the believer’s mirror, and the believer is the believer’s brother who guards him against loss and protects him when he is absent.
Grade: Hasan

Hadith #4937 - Sunan Abi Dawud - Alqama bin Mrthd علقمة بن مرثد; Burayda bin al-Husayb; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Sulaiman bin Burayda bin al-Husayb سليمان بن بريدة بن الحصيب; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
We came to Medina and stayed with Banu al-Harith b. al-Khazraj. She said : I swear by Allah, I was swinging between two date-palms. Then my mother came down; and I had my hair up to the ears. The transmitter then rest of the tradition.
Grade: Hasan Sahih

Hadith #4945 - Sunan Abi Dawud - Hudhayfah ibn al-Yaman; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Raba'i bin Harash bin Jahsh ربعي بن حراش; Sa'd bin Tariq, Abu Malik سعد بن طارق بن أشيم أبو مالك الأشجعي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
I swore allegiance to the Messenger of Allah (ﷺ) promising to hear and obey, and behave sincerely towards every Muslim. AbuZur’ah said: Whenever he sold and bought anything, he would say: What we took from you is dearer to us than what we gave you. So choose (as you like).
Grade: Sahih

Hadith #4979 - Sunan Abi Dawud - Abdul 'Aziz bin Rafi' عبد العزيز بن رفيع; Adi ibn Hatim al-Tayyi'; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
None of you should say Ja’shat nafsi (My heart is being agitated), but one should say Laqisat nafsi (My heart is being annoyed).
Grade: Sahih

Hadith #4982 - Sunan Abi Dawud - Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; ibn Umar; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Uthman bin Muhammad (Sunan Abi Dawud)
I was riding on a mount behind the prophet (May peace be upon him). It stumbled. Thereupon I said: May the devil perish! He said: do not say; may the devil perish! For you say that, he will swell so much so that he will be like a house, and say: by my power. But say: in the name of Allah; for when you say that, he will diminish so much so that he will be like a fly.
Grade: Sahih

Hadith #5025 - Sunan Abi Dawud - Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Abi Dawud)
The Prophet (ﷺ) said: One night it seemed to me in a dream that we were in the house of Uqbah ibn Rafi’ and were brought some of the fresh dates of Ibn tab. I interpreted it as meaning that to us is granted eminence (rif’ah) in this world, a blessed hereafter (‘aqibah), and that our religion has been good (tabah).
Grade: Sahih

Hadith #5036 - Sunan Abi Dawud - Abu Barda bin Abi Musa al-Asha'ari أبو بردة / الحارث بن أبي موسى الأشعري; Abu Musa al-Asha'ari; Hakeem bin al-Daylm حكيم بن الديلم; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Uthman bin Muhammad; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Abi Dawud)
The Prophet (ﷺ) said: Invoke a blessing on one who sneezes three times; (and if he sneezes more often), then if you wish to invoke a blessing on him, you may invoke, and if you wish (to stop), then stop.
Grade: Da'if

Hadith #5041 - Sunan Abi Dawud - ibn Abbas; Karayb bin Abi Muslim كريب بن أبي مسلم الهاشمي; Salmah bin Kahayl al-Hadrami سلمة بن كهيل بن حصين; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Uthman bin Muhammad; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Abi Dawud)
The Prophet (ﷺ) said: If anyone spends the night on the roof of a house with no stone palisade, Allah’s responsibility to guard him no longer applies.
Grade: Sahih

Hadith #5047 - Sunan Abi Dawud - Abdul Malik bin 'Umayr al-Qabti عبد الملك بن عمير بن سويد القبطي; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Hudhayfah ibn al-Yaman; Raba'i bin Harash bin Jahsh ربعي بن حراش; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Abi Dawud)
The Messenger of Allah (May peace be upon him) said to me: when you go to bed while you are in the state of purification, lay your head on your right hand. He then mentioned the rest of the tradition in a similar manner as above.
Grade: Sahih

Hadith #5097 - Sunan Abi Dawud - Abdur Rahman bin Mahdi عبد الرحمن بن مهدي; al-Mqdam bin Shryh bin Han'i المقدام بن شريح بن هانئ بن يزيد; Muhammad bin Bashar Bindar محمد بن بشار بندار; Sharih bin Hani' al-Harithi شريح بن هانئ; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
I heard the Messenger of Allah (ﷺ) say: The wind comes from Allah’s mercy. Salamah’s version has: It is Allah’s mercy; it (sometimes) brings blessing and (sometimes) brings punishment. So when you see it, do not revile it, but ask Allah for some of its good, and seek refuge in Allah from its evil.
Grade: Sahih

Hadith #5103 - Sunan Abi Dawud - Abu Rafi'; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Ubaidullah bin Abi Rafi' عبيد الله بن أبي رافع; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
The Prophet (ﷺ) said: When you hear the barking of dogs and the braying of asses at night, seek refuge in Allah, for they see which you do not see.
Grade: Sahih

Hadith #5116 - Sunan Abi Dawud - Abdullah bin Dinar عبد الله بن دينار العدوي; Abdur Rahman bin 'Abdullah bin Dinar عبد الرحمن بن عبد الله بن دينار; Abu 'Amir al-'Aqdi عبد الملك بن عمرو القيسي أبو عامر العقدي; Muhammad bin Bashar Bindar محمد بن بشار بندار; Smak bin Hrb bin Aws سماك بن حرب بن أوس; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Prophet (ﷺ) said: Allah, Most High, has removed from you the pride of the pre-Islamic period and its boasting in ancestors. One is only a pious believer or a miserable sinner. You are sons of Adam, and Adam came from dust. Let the people cease to boast about their ancestors. They are merely fuel in Jahannam; or they will certainly be of less account with Allah than the beetle which rolls dung with its nose.
Grade: Hasan

Hadith #5127 - Sunan Abi Dawud - Abu Mas'ud al-Badri; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sa'd bin Iyas, Abu 'Amr Shaybani سعد بن إياس أبو عمرو الشيباني; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Sulaiman al-A'mash الأعمش / سليمان بن مهران (Sunan Abi Dawud)
I never saw the Companions of the Messenger of Allah (May peace be upon him) so happy about anything as I saw them happy about this thing. A man said : Messenger of Allah! A man loves another man for the good work which he does, but he himself cannot do like it. The Messenger of Allah (May peace be upon him) said: A man will be with those whom he loves.
Grade: Sahih

Hadith #5129 - Sunan Abi Dawud - Abu Musa al-Asha'ari; Bryd bin 'Abdullah بريد بن عبد الله بن أبي; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
A man came to the prophet (May peace be upon him) and said: Messenger of Allah! I have been left without a mount. So give me a mount. He replied: I have no mount to give, but go to so and so; he may perhaps give you a mount. He then went to him and he gave him a mount. He came to the Messenger of Allah (May peace be upon him) and informed him about it. Thereupon the Messenger of Allah (May peace be upon him) said: if anyone guides someone to a good (deed), he will get the reward like the reward
Grade: Sahih

Hadith #5135 - Sunan Abi Dawud - Abu Hurairah; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Suhayl bin Abi Salah سهيل بن أبي صالح (Sunan Abi Dawud)
Al-Ala b. al-Hadrami wrote to the prophet (May peace be upon him), and he began with his name.
Grade: Da'if

Hadith #5137 - Sunan Abi Dawud - Bahz bin Hakim bin Mu'awiya al-Qushayri بهز بن حكيم بن معاوية; Hakeem bin Mu'awiyya bin Hayda حكيم بن معاوية بن حيدة القشيري; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
A son does not repay what he owes to his father unless he buys him and emancipates him if he finds him in slavery.
Grade: Sahih

Hadith #5150 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; Muhammad bin 'Isa bin Hyan محمد بن عيسى بن حيان; Mujahid bin Jabir مجاهد بن جبر; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
Sahl (b. Sa’d) reported the prophet (May peace be upon him) as saying; I and the one who takes the responsibility of an orphan will be in Paradise thus, and he joined his middle finger and forefinger.
Grade: Sahih

Hadith #5165 - Sunan Abi Dawud - Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Mu'awiya bint Suwayd al-Mazni; Salmah bin Kahayl al-Hadrami سلمة بن كهيل بن حصين; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
Abu al-Qasim, the Prophet of Atonement (ﷺ) said to me: If anyone reviles his slave when he is innocent of what he said, he will be beaten on the Day of Resurrection. The transmitter Mu’ammal said: ‘Isa narrated it to us from al-Fudial, that is, Ibn Ghazwan.
Grade: Sahih

Hadith #5173 - Sunan Abi Dawud - Harun bin 'Abdullah al-Hamal هارون بن عبد الله بن مروان الحمال; Sa'd ibn Abi Waqqas; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Sulaiman al-A'mash الأعمش / سليمان بن مهران; Talha bin Msrf bin 'Amr طلحة بن مصرف بن عمرو بن كعب; Umar bin Sa'd bin 'Ubaid عمر بن سعد بن عبيد أبو داود (Sunan Abi Dawud)
The Prophet (ﷺ) said: When one has a look into the house, then there is no (need of) permission.
Grade: Da'if

Hadith #5216 - Sunan Abi Dawud - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
when he came near the mosque, he said to the Ansar; stand up showing respect to your chief.
Grade: Sahih

Hadith #5246 - Sunan Abi Dawud - Abu Hurairah; Muhammad bin Ajlan al-Madni محمد بن عجلان المدني; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
Do not leave a fire burning in your houses while you are asleep.
Grade: Sahih

Hadith #5250 - Sunan Abi Dawud - al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; ibn Umar; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Salim bin 'Abdullah bin 'Umar سالم بن عبد الله بن عمر بن الخطاب; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Prophet (ﷺ) said: He who leaves the snakes along through fear of their pursuit, does not belong to us. We have not made peace with them since we have fought with them.
Grade: Sahih

Hadith #5267 - Sunan Abi Dawud - Muhammad bin 'Abdur Rahman b. Abi Dh'ab محمد بن عبد الرحمن بن أبي ذئب; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Prophet (ﷺ) prohibited to kill four creatures: ants, bees, hoopoes, and sparrow-hawks.
Grade: Sahih